Transparency dilemma in interpersonal relationships - Rehman, Sharaf (Journal of Gender and Power, 2020)
Humans as social animals move from being strangers to becoming intimate by taking risks of engaging in self-disclosure—from sharing insignificant bits of information to details about their beliefs, opinions, lifestyles, prejudices, and values. Romantic and intimate relationships come about when players peel away their outer layers and allow others to get closer to their core. However, as couples become more familiar, they experience certain tensions known as relational dialectics. These are autonomy versus connection, novelty versus predictability, and openness versus transparency (openness). This paper presents the findings of a survey of the perceptions about these tensions among the Hispanic-America college students (N=108). The subjects rank-order these tensions in terms of their importance, and the level of difficulty in dealing with the tensions.